Use of a donor‐derived cell‐free DNA assay to monitor treatment response in pediatric renal transplant recipients with allograft rejection. (27th March 2022) - Steggerda, Justin A.; Pizzo, Helen; Garrison, Jonathan; Zhang, Xiaohai; Haas, Mark; Kim, Irene K.; Jordan, Stanley C.; Puliyanda, Dechu P.
Abstract: Background: Detection of donor‐derived cell‐free DNA (dd‐cfDNA) reliably identifies allograft rejection in pediatric and adult kidney transplant (KT) recipients. Here, we evaluate the utility of dd‐cfDNA for monitoring response to treatment among pediatric renal transplant recipients suffering graft rejection. Methods: 58 pediatric transplant recipients were enrolled between April 2018 and March 2020 and underwent initial dd‐cfDNA testing to monitor for rejection. Allograft biopsy was performed for dd‐cfDNA scores >1.0%. Patients with histologically proven rejection formed the study cohort and underwent appropriate treatment. Results of dd‐cfDNA, serum creatinine (SCr), biopsy findings, and treatment outcomes were evaluated. Standard statistical analyses were applied. Results: Nineteen of 58 (31%) patients had dd‐cfDNA score >1.0%, of which 18 (94.7%) had biopsy‐proven rejection. Median dd‐cfDNA value was 1.90% (interquartile range 1.43%–3.23%), and biopsy results showed 11 patients (61.1%) with antibody‐mediated rejection (AMR), 2 patients (11.1%) with T‐cell mediated rejection (TCMR), and 5 patients (27.7%) with mixed AMR/TCMR. SCr at time of biopsy was 1.28 ± 1.09 mg/dl. Following treatment, dd‐cfDNA scores decreased for all types of rejection but still remained >1.0% in both AMR (1.50% [0.90%–3.10%]) and mixed (1.40% [0.95%–4.15%]) groups. Repeat dd‐cfDNA values were <1.0% for patients with TCMR (0.20%–0.28%). SCr showed minimal change from pre‐treatment levels regardless of rejection subtype. Conclusions: Patients with TCMR may be reliably followed by dd‐cfDNA; however, it remains unclear whether persistently elevated dd‐cfDNA levels in AMR is a reflection of ongoing subclinical rejection or an inherent limitation of the assay's utility.